From Molecules to Minds: Ontological and Epistemological Perspective of Global Warming and The Implementation in Science Education - Sarah, Lia Laela; Suhandi, Andi; Nahadi, Nahadi; Anwar, Sjaeful (Journal of Science Education Research, 2025)
The study was a qualitative research, employing ontological and epistemological approaches to explore the philosophy of global warming. Questionnaires and interviews were conducted with students and teachers, which examined whether the current implementation of global warming education aligns with ontological and epistemological perspective and propose recommendations to improve global warming education in science lesson. The ontological perspective begins with literature review that examines the unique of greenhouse gasses characterized as heat traps, focusing on microscopic view of vibrational modes of molecules and their impact on global warming. Furthermore, the epistemological perspective explored how researchers validate the scientific understanding of global warming and its impact on the environment. In addition, the questionnaire result showed that various teaching method, such as experiment, video, PhET simulation, teacher explanation, and internet exploration, were used. But most of students never see the microscopic view of vibrational greenhouse gas molecules that trap the heat. Students also did not evaluate and validate the influence of greenhouse gas concentration on increasing system temperature as epistemological approach. Therefore, the lesson of global warming especially the concept of greenhouse effect, needs an approach that integrates ontological and epistemological perspective, such integrating modeling or simulation in microscopic scale into experimental activities (bifocal modeling).